Metacognitive Training for Depression: Feasibility, safety and acceptability of two new treatment modules to reduce suicidality. (1st December 2020) - Jelinek, Lena; Peth, Judith; Runde, Anne; Arlt, Sönke; Scheunemann, Jakob; Gallinat, Jürgen
Abstract: Recent evidence favours psychological interventions explicitly targeting suicidality; however, group treatments on suicidality are rare and are assumed to have unfavourable effects. We developed two modules specifically addressing suicidality that replace two existing modules in the Metacognitive Training for Depression (D‐MCT). The aim of the current study was to examine the feasibility, safety, and acceptability of this intervention (D‐MCT/S). Forty‐eight inpatients with depression received eight sessions of D‐MCT/S over 4 weeks in addition to standard treatment. Patients were assessed before the training, 4 and 8 weeks later regarding suicidality (primary outcome: Beck Suicide Scale [BSS]), hopelessness, depression (e.g. Hamilton Depression Rating Scale [HDRS]), dysfunctional attitudes, and self‐esteem. Negative effects of the modules and subjective appraisal were assessed. Suicidality, hopelessness, and depression decreased over time. Whereas the effects on the BSS only reached trend level, a large effect was observed when the suicide item of the HDRS was used. Two of the 46 patients (4%) reported a deterioration in their symptoms, but this was not associated with the D‐MCT/S. Negative effects of the general training were rather low, and acceptability was high. In general, patients evaluated the two new modules on suicidality similarly to the established modules. However, both modules were assessed as distressing by 39% of the patients. When we addressed suicidality in the D‐MCT/S, we did not observe any contagious effects. In fact, the pilot versions of the two modules on suicidality are promising in terms of feasibility, safety, and acceptability. The results will be used to improve current shortcomings. The trial was registered with the German Clinical Trials Register (#DRKS‐ID: DRKS00010543) on 23 August 2016.